Method for Forecasting Transport Properties of Working Substances used in Industrial Thermal Power System - V. S. Eldarov; I. I. Vahabov; A. L. Bahtijarov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
On the basis of the analysis of the literary data on heat conductivity of water solutions of salts at high temperatures, pressure and concentration the following generalizing formula is received.